2006
DOI: 10.3748/wjg.v12.i29.4614
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal mucosal adaptation

Abstract: Intestinal failure is a condition characterized by malnutrition and/or dehydration as a result of the inadequate digestion and absorption of nutrients. The most common cause of intestinal failure is short bowel syndrome, which occurs when the functional gut mass is reduced below the level necessary for adequate nutrient and water absorption. This condition may be congenital, or may be acquired as a result of a massive resection of the small bowel. Following resection, the intestine is capable of adaptation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 190 publications
1
71
0
6
Order By: Relevance
“…In light of these previous studies, the changes we observed in colonic SCFA concentrations and microbiota composition suggest that feeding RS may have important effects on host metabolic processes in the young. The microbiota-mediated effect on host metabolism is further supported by the increased colonic-crypt length seen in RS-fed rats, which is indicative of increased intestinal growth and absorptive capacity (7,26). The importance of the microbiota to host metabolism was also illustrated by the observation that germ-free rats ate more food but gained less weight than conventional rats fed the same diets.…”
Section: Discussionmentioning
confidence: 93%
“…In light of these previous studies, the changes we observed in colonic SCFA concentrations and microbiota composition suggest that feeding RS may have important effects on host metabolic processes in the young. The microbiota-mediated effect on host metabolism is further supported by the increased colonic-crypt length seen in RS-fed rats, which is indicative of increased intestinal growth and absorptive capacity (7,26). The importance of the microbiota to host metabolism was also illustrated by the observation that germ-free rats ate more food but gained less weight than conventional rats fed the same diets.…”
Section: Discussionmentioning
confidence: 93%
“…One such condition is the adaptation response of the remnant bowel to massive intestinal loss (24). During adaptation, enterocyte proliferation is triggered for the generation of taller villi, thereby augmenting the intestinal surface area for digestion and absorption.…”
Section: Discussionmentioning
confidence: 99%
“…Protein deficiency, however, changes the intestinal architecture without altering its absorption capacity. The absorption capacity is preserved with physiological adaptation and change in the turnover rate of the enterocytes (Drozdowski and Thomson, 2006). The data obtained from the intestinal measurements carried out in our study show that the administration of AKG acid affects the intestinal adaptation, but not the absorption capacity, in rats fed a PFD.…”
Section: Intestinal Tractmentioning
confidence: 47%